Increased isolation of nontuberculous mycobacteria among TB suspects in Northeastern, Tanzania: public health and diagnostic implications for control programmes. (December 2016) - Hoza, Abubakar; Mfinanga, Sayoki; Rodloff, Arne; Moser, Irmgard; König, Brigitte
Abstract Background Non-tuberculous mycobacteria (NTM) are increasingly reported worldwide associated with human disease. Defining the significance of NTM in settings with endemic tuberculosis (TB) requires the discrimination of NTM from TB in suspect patients. Correct and timely identification of NTM will impact both therapy and epidemiology of TB and TB-like diseases. The present study aimed at determining the frequency and diversity of NTM among TB suspects in northeastern Tanzania. Methods A cross-sectional study was conducted between November 2012 through January 2013. Seven hundred and forty-four sputum samples were collected from 372 TB suspects. Detection was done by using phenotypic, GenoType® Mycobacterium CM/AS kits, 16S rRNA andhsp65 gene sequencing for identification of isolates not identified by Hain kits. Binary regression model was used to analyse the predictors of NTM detection. Results The prevalence of NTM was 9.7 % of the mycobacterial isolates. Out of 36 patients with confirmed NTM infection, 12 were HIV infected with HIV being a significant predictor of NTM detection (P < 0.001). Co-infection withMycobacterium tuberculosis (M. tb ) was found in five patients. Twenty-eight NTM isolates were identified using GenoType® Mycobacterium CM/AS and eight isolates could not be identified. Identified species includedM. gordonae andM. interjectum 6 (16.7 %), M. intracelullare 4 (11.1 %), M. avium spp. andM. fortuitum 2 (5.5 %), M. kansasii, M. lentiflavum, M. simiae, M. celatum, M. marinum 1 (2.8 %) each. Of isolates not identified to subspecies level, we identifiedM. kumamotonense (2), M. intracellulare/kansasii, M. intermedium/triplex, M. acapulcensis/flavescens, M. stomatepiae, M. colombiense andM. terrae complex (1) each using 16S rRNA sequencing. Additionally, hsp 65 gene sequencing identifiedM. kumamotonense, M. scrofulaceum /M. avium, M. avium, M. flavescens/novocastrense, M. kumamotonense /hiberniae, M. lentiflavum, M. colombiense/M. avium andM. kumamotonense/terrae/hiberniae (1) each. Results of the 16S rRNA andhsp 65 gene sequencing were concordant in three and discordant in five isolates not identified by GenoType® Mycobacterium CM/AS. Conclusion NTM infections may play a vital role in causing lung disease and impact management of TB in endemic settings. GenoType® Mycobacterium CM/AS represents a useful tool to identify clinical NTM infections. However, 16S rRNA gene sequencing should be thought for confirmatory diagnosis of the clinical isolates. Due to the complexity and inconsistence of NTM identification, we recommend diagnosis of NTM infections be centralized by strengthening and setting up quality national and regional infrastructure.